SIFAT PAPAN WOL KAYU DARI SEMBILAN-JENIS KAYU KALIMANTAN BARAT - I M Sulastiningsih; Rozak Memed; Paribotro Sutigno (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
The results of laboratory test of ioood-wool board properties made /Tont nine wood species obtained from West Ka• limantan province are reported in this paper. The properties tested were board density, moisture eontent.. thickness reduction due to compreuion and bending strength.The study revealed that the averageyield of uiood-taoo! was 365.4 kg per cubic meter of log input. The wood-wool of Shorea smithiana Sym. must be soaked in cold water for 24 hours prior to manufacturing of uood-uoo; board, whereaathe other apecieadid .not require soaking.The physical and mechanical properties of uiood-wool boards made from Bix wood apecies catalyzed either with CaCl2 solution or Ca(OH)2 BUBpenaion meet the DIN 1101 standard.